2013 International Conference on Biometrics (ICB) 2013
DOI: 10.1109/icb.2013.6612993
|View full text |Cite
|
Sign up to set email alerts
|

Sketch based face recognition: Forensic vs. composite sketches

Abstract: Facial sketches are widely used by law enforcement agencies to assist in the identification and apprehension of suspects involved in criminal activities. Sketches used in forensic investigations are either drawn by forensic artists (forensic sketches) or created with computer software (composite sketches) following the verbal description provided by an eyewitness or the victim. These sketches are posted in public places and in media in hopes that some viewers will provide tips about the identity of the suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 23 publications
0
24
0
2
Order By: Relevance
“…This publication extends upon the work in [6] in the following ways: (i) the background database is increased to 100,000 versus 10,000 in [6], (ii) integrated and generalized the approaches in [6], [17], [14] and [21] into a unified framework, (iii) improved algorithms such that the recognition performance is comparable to [6] after increasing the background gallery size by an order of magnitude, (iv) evaluated the FaceSketchID System on the largest reported collection of operational (composite, mugshot) pairs reported in the literature, (v) evaluated the effect of the type of training data on the performance of our recognition system, and (vi) demonstrated that composites made from poor quality surveillance imagery can be used to identify the suspect that could not be identified based on the original image.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…This publication extends upon the work in [6] in the following ways: (i) the background database is increased to 100,000 versus 10,000 in [6], (ii) integrated and generalized the approaches in [6], [17], [14] and [21] into a unified framework, (iii) improved algorithms such that the recognition performance is comparable to [6] after increasing the background gallery size by an order of magnitude, (iv) evaluated the FaceSketchID System on the largest reported collection of operational (composite, mugshot) pairs reported in the literature, (v) evaluated the effect of the type of training data on the performance of our recognition system, and (vi) demonstrated that composites made from poor quality surveillance imagery can be used to identify the suspect that could not be identified based on the original image.…”
Section: Related Workmentioning
confidence: 99%
“…However, matching facial composites to photographs is 5 http://www.nist.gov/itl/iad/ig/frvt-home.cfm a more challenging problem with only a limited amount of published work, some of which include: [7], [8], [11], [16], [10], [14], [15], [18], [17], [6]. Of these, most studies have used composites drawn while viewing the mugshot or photograph (viewed hand-drawn composites).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations